COMPOSITION OF CREDIT PROVISIONS IN COMMERCIAL BANKS AND RISKS IN THEIR MANAGEMENT - Eshboyev Shakhobiddin (Scholar Express Journals, 2024)
The structure of credit investments in commercial banks and risks in their management are considered. Also, the importance of credit risks,important elements of reducing credit risks in commercial banks are given. In recent years, after the global financial crisis, the issue of credit risk management has received increased attention from international regulators. Credit risk management frameworks are often not sufficiently integrated within the organization, there is no unified approach, and there is no holistic view of all risks. Likewise, where they exist, sound risk management practices have helped institutions to weather financial crises better than others.
Keywords: Bank; credit; risk; monetization coefficient